Kebebasan Beragama Di Indonesia Dalam Konteks Keberagaman Sosial - Faturohman Faturohman; Yus Safarudin; Yayan Yayan (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Abstract Freedom of religion is one of the fundamental human rights that is internationally recognized and regulated in various national legal instruments. Freedom of religion is an important aspect in the context of Indonesia's social and cultural diversity. This article examines the condition of religious freedom in Indonesia, the challenges faced, as well as the legal and human rights implications that accompany it. The main focus is given to the analysis of legal regulations, incidents of human rights violations in religious freedom, and efforts to protect religious rights. A multidimensional approach is used to analyze various factors that influence religious freedom, including legal, political, social and cultural aspects. challenges such as intolerance, discrimination and interreligious conflict are the main focus in this analysis. Prospects for strengthening religious freedom, including efforts to strengthen legal protection and the promotion of interfaith dialogue, should be well advanced. This research aims to provide an in-depth understanding of the dynamics of religious freedom in Indonesia and offer policy recommendations that can help create an inclusive and just environment for all religious communities. Thus, it is hoped that this research can make a significant contribution in advancing issues of religious freedom and strengthening the foundations of democracy and pluralism in Indonesia.